Assessment of the wettability of addition silicone Impression material following short term immersion in tea tree oil solution - Samir Samier hammed; Samir Samier hammed; Aseel Mohammed Al-Khafaji ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Background: Dental impressions are often contaminated with the patient’s saliva, blood, and plaque, represents a risk of cross-infection between dental practitioners. In order to prevent the spread of microorganisms, disinfection of all dental impressions is mandatory. Chemicals are usually used to disinfect impressions by immersion. Nonetheless, these chemicals may alter the physical and mechanical properties of impression material. The study purpose was to evaluate the tea tree oil effect as an impression disinfectant on wettability property of addition silicone impressions material.This study employed a total of 60 heavy- and light-body addition silicon impression material specimens. The specimens were randomly sorted and immersed into three primary groups. These test groups where 1% TTO and the other two groups are distilled water (negative control) and 2% glutaraldehyde (positive control).all was immersed for 10 minutes .each of the three main groupings has 20 specimens.There were no statistically significant differences in wettability of addition silicone impressions among all test groups.The addition silicone impression material may be safely submerged in TTO for 10 minutes to disinfect it without impairing the wettability of the impression.DOI: https://doi.org/10.54633/2333-024-056-008